« On ne peut lutter contre la poussée de l’Esprit » : les mulieres religiosae des Pays-Bas méridionaux du xiiie siècle, un contre-pouvoir ? - Anne-Laure Méril-Bellini Delle Stelle (Les Cahiers de Framespa)
This article uses the thirteenth century Vitae of the mulieres religiosae from the Southern Low Countriesto analyze their female spiritual power flourishing at the same time with the male priesthood. Described by reforming clerics, it is limited to a few strange spiritual practices and comes together with the power of the Church, without competing. In the course of the thirteenth century, the ecclesial institution challenge this male/female, secular/clerical deal.